Penerapan Manajemen Risiko dan Antisipasi Fluktuasi Nilai Tukar Terhadap Keberlangsungan Bisnis Pada UMKM Sektor Fashion di Kabupaten Bandung - Muhammad Nazwa Maurifa; Dwi Urip Wardoyo (Jurnal Manajerial, 2026)
Background – This research is motivated by the important role of Micro, Small, and Medium Enterprises (MSMEs), particularly the fashion sector, in supporting regional economic growth such as Bandung Regency. In running their businesses, MSMEs face various challenges that can impact business continuity, both from internal and external factors. One crucial internal factor is the ability of business actors to manage risks effectively through the implementation of risk management. Meanwhile, from the external side, fluctuations in the rupiah exchange rate also have the potential to impact business stability, especially for MSMEs that depend on imported raw materials. However, not all MSMEs have the same level of sensitivity to exchange rate changes, especially for businesses oriented towards the domestic market. This condition encourages the need for a more in-depth study of the influence of risk management and anticipation of exchange rate fluctuations on MSME business continuity. Aim – Based on this background, this study aims to analyze the influence of risk management on the sustainability of MSME businesses in the fashion sector, examine the influence of anticipating fluctuations in the rupiah exchange rate on business sustainability, and test the influence of both variables simultaneously on the sustainability of MSME businesses in Bandung Regency. Design / methodology / approach – This research employed a quantitative approach with a survey method. Data were collected through questionnaires distributed to 35 respondents, representing MSMEs in the fashion sector in Bandung Regency. The data were then analyzed using validity, reliability, normality, and multiple linear regression analysis using SPSS software. This approach was chosen to obtain an empirical picture of the relationships between variables in a measurable and objective manner. Findings – The results of the study indicate that the research instrument is valid and reliable, and the data are normally distributed. Partially, risk management has a positive and significant effect on business sustainability, meaning that better risk management increases the likelihood of business survival. Conversely, anticipation of exchange rate fluctuations does not have a significant effect. However, both variables simultaneously influence business sustainability, and most of the variation in business sustainability can be explained by both. These findings indicate that risk management is a key factor that MSMEs need to prioritize in maintaining business sustainability. Meanwhile, exchange rate fluctuations have not been a primary concern, especially for MSMEs focused on the domestic market. Therefore, improving risk management capabilities is a crucial strategic step for business sustainability. Conclusion - This study concludes that risk management plays a crucial role and is a key factor in determining the business sustainability of MSMEs in the fashion sector. Meanwhile, anticipating rupiah exchange rate fluctuations has not shown a significant partial impact, particularly for MSMEs focused on the domestic market. However, both variables collectively contribute to business sustainability. Therefore, strengthening risk management is a key strategy that MSMEs need to prioritize to maintain stability and prevent business disruption. Research implication – The implications of this study indicate that risk management is a key factor that MSMEs need to consider in maintaining business continuity. Therefore, business actors are advised to increase their capacity to manage risk, both financially, operationally, and market-based. For the government and policymakers, the results of this study can serve as a basis for designing MSME development programs that emphasize strengthening risk management. Theoretically, these findings also reinforce the view that internal factors have a more dominant influence than external factors in the context of MSMEs oriented towards the domestic market. Limitations – This study has several limitations. The relatively small number of respondents, 35, limits the generalizability of the results. Furthermore, this study focused solely on MSMEs in the fashion sector in Bandung Regency, so the results may not be applicable to other sectors or regions. The variables used were also limited to risk management and rupiah exchange rate fluctuations, thus not including other potentially influential factors, such as innovation, digitalization, and access to capital. Furthermore, the use of a quantitative approach prevented this study from delving deeply into the behavioral aspects and strategies of MSME actors in dealing with business risks.